Environmental factors and hygiene behaviors associated with facial cleanliness and trachoma in Kongwa, Tanzania - Xinyi Chen (Public Library of Science (PLoS), 2021)
Background Having a clean face is protective against trachoma. In the past, long distances to water were associated with unclean faces and increased trachoma. Other environmental factors have not been extensively explored. We need improved clarity on the environmental factors associated with facial cleanliness and trachoma prevalence, especially when the disease burden is low. Methodology/Principle findings A cross-sectional survey focusing on household environments was conducted in all 92 villages in Kongwa, Tanzania, in a random selection of 1798 households. Children aged 0–5 years in these households were examined for facial cleanliness. In each of the 50 randomly-selected villages, 50 children aged 1–9 years were randomly selected and examined for trachoma. In a multivariate model adjusting for child age, we found that children were more likely to have clean faces if the house had a clean yard (OR 1.62, 95% CI 1.37–1.91), an improved latrine (OR 1.11, 95% CI 1.01–1.22), and greater water storage capacity (OR 1.02, 95% CI 1.00–1.04), and if there were clothes washed and drying around the house (OR 1.30, 95% CI 1.09–1.54). However, measures of crowding, wealth, time spent on obtaining water, or the availability of piped water was not associated with clean faces. Using a cleanliness index (clean yard, improved latrine, washing clothes, ≥1 child in the household having a clean face), the community prevalence of trachoma decreased with an increase in the average value of the index (OR 2.28, 95% CI 1.17–4.80). Conclusions/Significance Access to water is no longer a significant limiting factor in children’s facial cleanliness in Kongwa. Instead, water storage capacity and the way that water is utilized are more important in facial cleanliness. A household cleanliness index with a holistic measure of household environment is associated with reduced community prevalence of trachoma. Author summary Trachoma, a leading cause of blindness, is caused by repeated infection that is spread from person to person via contaminated ocular and nasal discharge. Having a clean face is protective against trachoma. In the past, long distances to water were associated with unclean faces. Other environmental elements have not been extensively explored. We need improved clarity on the environmental factors affecting facial cleanliness and trachoma prevalence, especially when the disease burden is low but still above 5%. We conducted a household survey in every village in Kongwa district, Tanzania, and found that access to water has significantly improved and is no longer a limiting factor in children’s facial cleanliness. When households have more storage capacity for water used for washing, wash their clothes frequently and clean their yards, young children in the households are more likely to have clean faces. We then created a household cleanliness index that comprises a clean yard, washed clothes, an improved latrine and at least one child in the household having a clean face. We found that an increased average index score in the community is associated with a decreased prevalence of trachoma, suggesting that a multi-pronged approach to improve household cleanliness is valuable.